Some Aspects on 2-fuzzy 2-anti Continuous and Bounded Functions - Thangaraj Beaula; Beulah Mariya (International Journal of Mathematics And its Applications, 2017)
In this paper various types of 2-fuzzy 2-anti continuity and 2-fuzzy 2- anti boundedness are defined. Relationships between the types of 2-fuzzy 2-anti continuities are developed. Further the inter and intra relationship between strongly, weakly boundedness are studied.